2022
DOI: 10.1186/s12877-021-02728-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with 90-day acute ischemic stroke in patients ≥70 years old with total hip arthroplasty for hip fracture

Abstract: Background Postoperative ischemic stroke is a devastating complication following total hip arthroplasty (THA). The purpose of the current study was to investigate the incidence of postoperative acute ischemic stroke (AIS) in patients ≥70 years old with THA for hip fracture after 90 days and independent risk factors associated with 90-day AIS. Methods A multicenter retrospective study was conducted, patients ≥70 years old with THA for hip fracture u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Variability in hypertension prevalence, age distribution, and research settings could explain these disparities. Similarly, Atzmon et al 10 and He et al 18 identified atrial fibrillation as an independent predictor of post-fracture stroke; however, this meta-analysis found a non-significant trend 10 , 18 . These discrepancies again highlight that the synthesized data may fail to capture the nuanced effects detectable in higher-quality primary studies.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Variability in hypertension prevalence, age distribution, and research settings could explain these disparities. Similarly, Atzmon et al 10 and He et al 18 identified atrial fibrillation as an independent predictor of post-fracture stroke; however, this meta-analysis found a non-significant trend 10 , 18 . These discrepancies again highlight that the synthesized data may fail to capture the nuanced effects detectable in higher-quality primary studies.…”
Section: Discussionmentioning
confidence: 59%
“…Although hypertension, heart disease, atrial fibrillation, and renal insufficiency were not statistically significant predictors of stroke, understanding the nuances of an individual patient's comorbidity profile can still help guide personalized prevention tactics 29 . Low serum albumin levels have emerged as a potential novel biomarker for heightened stroke risk and warrants further research 18 . The incorporation of albumin testing into hip fracture care pathways may be useful in risk stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment is required in most patients who sustain hip fractures 4 , 5 . The choice of anaesthesia technique is crucial because it significantly influences the recovery after surgery and the risk of complications, especially in older patients 6 . However, the optimal anaesthetic technique for elderly patients with hip fracture has remained controversial for decades 7 .…”
Section: Introductionmentioning
confidence: 99%